Core Shell Nanostructure: Impregnated Activated Carbon as Adsorbent for Hydrogen Sulfide Adsorption - Nurul Noramelya Zulkefli; Rajeevelosana Seladorai; Mohd Shahbudin Masdar; Nabilah Mohd Sofian; Wan Nor Roslam Wan Isahak (Molecules, 2022)
This study focuses on the synthesis, characterization, and evaluation of the performance of core shell nanostructure adsorbent for hydrogen sulfide (H2S) capture. Commercial coconut shell activated carbon (CAC) and commercial mixed gas of 5000 ppm H2S balanced N2 were used. With different preparation techniques, the CAC was modified by core shell impregnation with zinc oxide (ZnO), titanium oxide (TiO2), potassium hydroxide (KOH), and zinc acetate (ZnAC2). The core structure was prepared with CAC impregnated by single chemical and double chemical labelled with ZnAC2-CAC (single chemical), ZnAC2/KOH-CAC, ZnAC2/ZnO-CAC, and ZnAC2/TiO2-CAC. Then, the prepared core was layered either with KOH, TiO2, NH3, or TEOS for the shell. The synthesized adsorbents were characterized in physical and chemical characterization through scanning electron microscopy (SEM), thermal gravimetric analysis (TGA), and Brunauer-Emmett-Teller (BET) analyzers. Operation of the adsorber column takes place at ambient temperature, with absolute pressure at 1.5 bar. The H2S gas was fed into the column at 5.5 L/min and the loaded adsorbents were 150 g. The performance of synthesized adsorbent was analyzed through the adsorbent’s capability in capturing H2S gas. Based on the results, ZnAc2/ZnO/CAC_WOS shows a better adsorption capacity with 1.17 mg H2S/g and a 53% increment compared to raw CAC. However, the degradation of the adsorbents was higher compared to ZnAc2/ZnO/CAC_OS and to ZnAc2/ZnO/CAC_WS ZnAc2/ZnO/CAC_OS. The presence of silica as a shell has potentially increased the adsorbent’s stability in several cycles of adsorption-desorption.